Sesquiterpene lactone derivatives of KSL-B targeting Arf1-Big1Sec7 interaction - Sergio Ortiz; François Peurois; Euzébio Guimarães Barbosa; Mohamed Selkti; Pascale Lemoine; Jacqueline Cherfils; Raphaël Grougnet; Sabrina Boutefnouchet (Elsevier, 2022)
The GDP/GTP conformational change of Arf GTPase proteins by different guanine exchange factor GEFs proteins (Big1Sec7, ARNOSec7, Brag1Sec7, etc.), modulates important eukaryotes cell functions, such as secretion, endocytosis, phagocytosis, cytokinesis and cell adhesion. The overproduction and overactivation of Arf1 (a member of the GTPase family) have been linked to tumour development and cancer cell proliferation. We herein report the identification of the natural sesquiterpene lactone ketopelenolide B (KSL-B, 1) as a moderate Arf1-Big1Sec7 inhibitor, evaluated by in silico (Inverse virtual screening) and in vitro (12.5 ​± ​1.3% of nucleotide exchange inhibition at 50 ​μM) approaches. Structural modifications by semisynthesis of 1 (2a-10) were then carried out and predicted in silico to retain the same binding mode. Biochemical assays in vitro detected an improvement in the nucleotide exchange inhibition by 8a to 32.0 ​± ​0.3% at 50 ​μM against Arf1-Big1Sec7 complex. In addition, 8a showed selectivity against others ArfGEF members (ARNOSec7 and BragSec7). This derivative may consequently be considered as a new hit targeting Arf1-Big1Sec7 complex with therapeutic potential, particularly in the field of parasitic diseases.